A synoptic review of Promonobothrium Mackiewicz, 1968 (Cestoda: Caryophyllidea), parasites of suckers (Catostomidae) in North America, with description of two new species - Oros, Mikulas; Brabec, Jan; Kuchta, Roman; Choudhury, Anindo; Scholz, Tomas (Folia parasitologica, 2016)
Monozoic cestodes of the recently amended genus Promonobothrium Mackiewicz, 1968 (Cestoda: Caryophyllidea), parasites of suckers (Cypriniformes: Catostomidae) in North America, are reviewed, with information on their host specificity, distribution and data on the scolex morphology of seven species studied for the first time using scanning electron microscopy (SEM). Evaluation of type and voucher specimens from museum collections and newly collected material of most species indicated the following valid nominal species: Promonobothrium minytremi Mackiewicz, 1968 (type species); P. ingens (Hunter, 1927); P. hunteri (Mackiewicz, 1963); P. ulmeri (Calentine et Mackiewicz, 1966); P. fossae (Williams, 1974) and P. mackiewiczi (Williams, 1974). Rogersus Williams, 1980 with its only species R. rogersi is transferred to Promonobothrium based on morphological and molecular data. Promonobothrium currani sp. n. and P. papiliovarium sp. n. are described from Ictiobus bubalus (Rafinesque) and Ictiobus niger (Rafinesque), and Erimyzon oblongus (Mitchill), respectively. The newly described species can be distinguished from the other congeners by the morphology of the scolex, the position of the anteriormost vitelline follicles and testes, the presence of postovarian vitelline follicles and the shape of the ovary. Molecular phylogenetic analyses of six species based on sequences of the small and large subunits of the nuclear ribosomal RNA genes (ssrDNA, lsrDNA) confirmed the monophyletic status of the genus and supported the validity of the species analysed. A key to identification of all species of Promonobothrium based on morphological characteristics is provided.
Keywords: Nearctic Region; taxonomy; North America; druhová specificita; DNA, Ribosomal; Phylogeny; Severní Amerika; Female; identification key; zvířata; comparative morphology; Eucestoda; máloostní; Cypriniformes; ženské pohlaví; fylogeneze; Species Specificity; ribozomální DNA; new species; Animals; molecular phylogeny; fish; Cestoda